Glucagon phosphorylates serine 552 of β-catenin leading to increased expression of cyclin D1 and c-Myc in the isolated rat liver. (July 2015) - Chowdhury, Md. Kamrul H.; Montgomery, Magda K.; Morris, Margaret J.; Cognard, Emmanuelle; Shepherd, Peter R.; Smith, Greg C.
Abstract In the last 20 years the prevalence of metabolic disorders, in particular type 2 diabetes (T2D), has more than doubled. Recently, a strong link between T2D and cancer, in particularly liver cancer has been reported. However, the mechanism connecting the development of type 2 diabetes and cancer remains unknown. One of the biggest drivers of liver cancer is alterations in the Wnt/β-catenin pathway. In this study, we aimed to identify the effect of glucagon on β-catenin in the isolated rat liver. We found glucagon, which is substantially raised in patients with T2D, rapidly phosphorylates β-catenin on serine 552 that is associated with increased expression of genes cyclin D1 (CCND1) and c-Myc (MYC), which are known to be involved in liver cancer. This finding may explain the increased risk of liver cancer in people with T2D.